Entrepreneurial Supply Chain Management in the Rural Production Cooperative and Joint-stock Farming Companies in North Khorasan Province: A Comparative Case Study - Mohammad Sharif Sharifzadeh; Mahdy yazdani; Gholamhossein Abdollahzadeh; Muhammad Reza Mahboobi (تعاون و کشاورزی, 2020)
The aim of this research was to compare the management of entrepreneurial supply chain in rural production cooperatives and joint-stock farming companies of North Khorasan province. The statistical population of the research included 4500 shareholders and members of 14 active companies. Sampling was performed in a multi-stage conducted and the sample size was determined using Cochran's formula (n=356). To collect the data, a researcher-made questionnaire was used. The content and formal validity of the questionnaire were established by an expert panel and its reliability confirmed based on Cronbach's alpha coefficient for different components (0.702 to 0.851). According to Friedmann's test results, the components of social network management, financial and investment management have the highest rank, and marketing and sales management, innovation, and technology acquisition management components have the lowest rank in the entrepreneurial supply chain of cooperatives and joint-stock companies, respectively. The correlation test showed that there is a significant positive relationship between all components of the entrepreneurial supply chain of the companies. Among them, the highest correlation was attained between the components of financial management and investment and sales and marketing management (0.679**) in cooperative companies and between the components of distribution management and production management (0.344**) in joint-stock companies. The results of the mean comparison test showed that production cooperatives performed better than joint-stock companies in conducting the components of input management, production management and marketing and sales management.